What in the world is going on? : 10 prophetic clues you cannot afford to ignore - Jeremiah, David (2008)
A unique book that cuts through the hundreds of books and numerous theories to identify the essential 10 most important bible prophecies.
Keywords: World politics -- Forecasting; International relations -- Forecasting; Civilization, Modern -- Forecasting; World politics; International relations -- History; Civilization, Modern